INTERNALISASI NILAI-NILAI PANCASILA DALAM PEMBENTUKAN KARAKTER ANAK USIA DINI MELALUI PERMAINAN LEGO - Nuzulur Rohmah; Pusparini, Dewi (Bunayya, 2026)
The study was conducted to analyse the implementation of Lego games to internalise the values of the 1945 Constitution of Indonesia in the formation of the character of children in early childhood. The study used a qualitative descriptive approach, conducted during the second semester of 2026 at RA Nahdlatul Ulum Pakes, with 16 preschool children as subjects. Data was collected through observation, interviews and documentation. The results of the study conducted by the researcher indicate that internalisation of the values of pancasila using lego games in a structured manner through group activities, discussions, role plays and joint task completion can internalise the values of pancasila, responsibility, gotong royong and musyawarah. This activity increases children's involvement and develops their ability to work together and communicate. However, some children were unable to participate optimally due to differences in character, self-confidence, and communication skills. This study shows the positive impact of Lego on children and demonstrates that it can be used as a relevant teaching strategy to support the formation of children's characters through meaningful learning.